(untitled) (Al-Qamar, 2019)
Nature has created both genders in quite balance and distributes their roles in equal proportion. But these days some unnatural demands by so called feminists have been raised in the favors of empowering women against men which has been giving rise to social disturbance, prejudice, anarchy and commotion in society. The purpose of this research is to bring into light the result of this confrontation. The analysis of collected data revealed that by reproaching the contribution of men and by looking for interchangeable roles, women cannot achieve that peace and pleasure which nature endows upon women rather such unnatural demands just giving rise to domestic stress, prejudice and discomfort and nothing else. Regarding the rights of women, Islam has always emphasized upon the rights of women and its practical applications and the chanted slogans are entirely undue and empty. The researcher has conducted the research in qualitative parading and its scope is fully pragmatic in nature.